Phase III Randomized Controlled Trial of eRAPID: eHealth Intervention During Chemotherapy. Issue 7 (1st March 2021) - Absolom, Kate; Warrington, Lorraine; Hudson, Eleanor; Hewison, Jenny; Morris, Carolyn; Holch, Patricia; Carter, Robert; Gibson, Andrea; Holmes, Marie; Clayton, Beverly; Rogers, Zoe; McParland, Lucy; et al.
Abstract : PURPOSE: Electronic patient self-Reporting of Adverse-events: Patient Information and aDvice (eRAPID) is an online eHealth system for patients to self-report symptoms during cancer treatment. It provides automated severity-dependent patient advice guiding self-management or medical contact and displays the reports in electronic patient records. This trial evaluated the impact of eRAPID on symptom control, healthcare use, patient self-efficacy, and quality of life (QOL) in a patient population treated predominantly with curative intent. METHODS: Patients with colorectal, breast, or gynecological cancers commencing chemotherapy were randomly assigned to usual care (UC) or the addition of eRAPID (weekly online symptom reporting for 18 weeks). Primary outcome was symptom control (Functional Assessment of Cancer Therapy-General, Physical Well-Being subscale [FACT-PWB]) assessed at 6, 12, and 18 weeks. Secondary outcomes were processes of care (admissions or chemotherapy delivery), patient self-efficacy, and global quality of life (Functional Assessment of Cancer Therapy–General, EQ5D-VAS, and EORTC QLQ-C30 summary score). Multivariable mixed-effects repeated-measures models were used for analyses. Trial registration: ISRCTN88520246. RESULTS: Participants were 508 consenting patients (73.6% of 690 eligible) and 55 health professionals. eRAPID compared to UC showed improved physical well-being at 6 ( P = .028) and 12 ( P = .039) weeks and no difference at 18 weeks (primary end point) ( P = .69). Fewer eRAPID patients (47%) had clinically meaningful physical well-being deterioration than UC (56%) at 12 weeks. Subgroup analysis found benefit in the nonmetastatic group at 6 weeks ( P = .0426), but not in metastatic disease. There were no differences for admissions or chemotherapy delivery. At 18 weeks, patients using eRAPID reported better self-efficacy ( P = .007) and better health on EQ5D-VAS ( P = .009). Average patient compliance with weekly symptom reporting was 64.7%. Patient adherence was associated with clinician's data use and improved FACT-PWB at 12 weeks. CONCLUSION: Real-time monitoring with electronic patient-reported outcomes improved physical well-being (6 and 12 weeks) and self-efficacy (18 weeks) in a patient population predominantly treated with curative intent, without increasing hospital workload.